2020
DOI: 10.1183/23120541.00589-2020
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic excursion correlates with exercise capacity and dynamic hyperinflation in COPD patients

Abstract: BackgroundAlthough the pathophysiological mechanisms involved in the development of dyspnoea and poor exercise tolerance in patients with chronic obstructive pulmonary disease (COPD) are complex, dynamic lung hyperinflation (DLH) plays a central role. Diaphragmatic excursions can be measured by ultrasonography (US) with high intra- and interobserver reliability. The objective of this study was to evaluate the effect of diaphragmatic excursions as assessed by US on exercise tolerance and DLH in patients with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…In addition, the model using DE max had better prediction performance than that using PI max . The high predictability of DE max may be because of its strong association with DLH and dyspnoea during exercise, as reported previously [9]. DLH is involved in the development of dyspnoea, and both are important factors to determine the improvement in 6MWD in patients with COPD.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In addition, the model using DE max had better prediction performance than that using PI max . The high predictability of DE max may be because of its strong association with DLH and dyspnoea during exercise, as reported previously [9]. DLH is involved in the development of dyspnoea, and both are important factors to determine the improvement in 6MWD in patients with COPD.…”
Section: Discussionsupporting
confidence: 57%
“…Using the liver as an acoustic window (Fig. 1A), a convex 3.5 MHz probe was used to measure the excursions of the right hemidiaphragm according to the techniques mentioned in previous studies [9,12,13]. The M-mode cursor was rotated and placed on the axis of diaphragmatic displacement on the stored image, and displacement measurements were performed.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LUS diaphragmatic excursion proved to predict successful weaning in critically ill patients during the acute phase of the disease [36], to the best of our knowledge, this is the first study to evaluate DT and DE values in fully recovered patients. Considering the proven role of these echo parameters in assessing a decreased exercise capacity and increased dyspnoea in COPD patients [37], they might as well predict the outcome of patients after COVID-19 pneumonia. However, considering the contrasting evidence on the results of pulmonary function tests after SARS-CoV-2-related pneumonia [38,39], prospective and more powered studies are mandatory to define the abnormal thresholds, feasibility and diagnostic power of such echo imaging techniques in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, DE was used to detect the respiratory problems that induced dyspnea (1). In the last few years, studies have shown that DE can be utilized in several aspects of detection and clinical assistance, i.e., the detection of phrenic-nerve-injury-induced diaphragmatic paralysis (3)(4)(5), the evaluation of chronic obstructive pulmonary disease (6)(7)(8), or chronic pulmonary disease patients (9), the assessment of respiratory function in post-thoracentesis (10), or chronic kidney disease patients with hemodialysis (11), the guided technique for ventilator use and weaning in critically ill patients (12)(13)(14), and as an intervention in the diaphragmatic pacing protocol for the appropriate stimulation of diaphragmatic muscle (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%